Development of the Pancasila Student Profile Strengthening Project Module (P5) Based on Pakpak Bharat Culture - Gafari, M Oky Fardian; Pulungan, Hendra K.; Astuti, Wahyu Wiji; Assalam, Muhammad Hafidz; Surip, Muhammad (Universitas Muhammadiyah Malang, 2024)
Teaching modules are written materials in the form of paper sheets that are bound and covered and present knowledge that is systematically arranged. This research aims to develop valid, effective, and practical teaching modules based on the culture of Pakpak Bharat Sumatra. This study uses a research and development (R&D) model with the ADDIE model with five main stages: analysis, design, development, implementation, and evaluation. This teaching module has been validated by 9 experts, namely material experts, media design experts, and linguists. The study had 2 trials: a small group trial (15 students) and a large group trial (45 students). Based on the combined percentage of validity of teaching modules, according to experts, 82% is categorized as